2005
DOI: 10.1111/j.1348-0421.2005.tb03752.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Categorization of Pathogenic Escherichia coli by Multiplex PCR

Abstract: Escherichia coli, which causes diarrhea in humans, can be classified into the following heterogenous groups: enterohemorrhagic E. coli (EHEC), enteropathogenic E. coli (EPEC), enteroaggregative E. coli (EAggEC), enteroinvasive E. coli (EIEC), and enterotoxigenic E. coli (ETEC). These diarrheagenic E. coli categories are differentiated on the basis of their infection and pathogenic mechanisms. Serotyping, phenotypic assays, and molecular detection assays are very useful in identifying these diarrheagenic E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 29 publications
3
35
0
3
Order By: Relevance
“…However, these methods alone are not sufficient to identify all five pathotypes of DEC (Brandal et al 2007). The genes encoding virulence factors are extensively studied and characterized, and several PCR methods have been developed to identify the virulence genes of DEC (Kimata et al 2005). Numerous multiplex PCR assays have been developed to identify DEC, and assays were recently described that are capable of distinguishing the five pathotypes of DEC (Aranda et al 2004, Nguyen et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods alone are not sufficient to identify all five pathotypes of DEC (Brandal et al 2007). The genes encoding virulence factors are extensively studied and characterized, and several PCR methods have been developed to identify the virulence genes of DEC (Kimata et al 2005). Numerous multiplex PCR assays have been developed to identify DEC, and assays were recently described that are capable of distinguishing the five pathotypes of DEC (Aranda et al 2004, Nguyen et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Detection assays rely on the amplification of eltA alone, eltA plus either sta1 or sta2, or all three toxin genes. [6][7][8][9][10][11][12][13][14][15][16] The DNA hybridization assay is a culture-dependent method that requires transfer of cultured lactose-positive colonies from MacConkey agar to Whatman filter paper (Fisher Scientific, Waltham, MA) followed by cell lysis and probe hybridization. Probes targeting ST P (sta1), ST H (sta2), and LT (eltA) are then used for ETEC detection 17,18 ; remarkably, many clinical manuscripts reporting the prevalence of ETEC use this less-sensitive DNA hybridization method or use PCR assays that target eltA plus only a single allele of ST. As a result, these studies are likely to have underestimated the prevalence of ETEC infections.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believe that a typical EAggEC possesses both aggR and pCVD432 genes that are present in the virulence plasmid pAA [17,18]. Kimata et al [19] identified AA was characterized by the prominent autoagglutination of bacterial cells as well as adherence to glass cover slips without HEp-2 cells. The sine qua non of AA, however, was the characteristic layering of the bacteria, best described as a stacked-brick configuration.…”
Section: Discussionmentioning
confidence: 99%